Acneiform eruptions: A common cutaneous toxicity of the MEK inhibitor trametinib. (9th December 2013) - Anforth, Rachael; Liu, Michael; Nguyen, Bao; Uribe, Pablo; Kefford, Richard; Clements, Arthur; Long, Georgina V; Fernandez‐Peñas, Pablo
Abstract Background The MEK inhibitor trametinib is currently undergoing clinical trials as the treatment of metastatic melanoma both alone and in combination with the BRAF inhibitor dabrafenib. One of the most frequent side‐effects associated with its use as a single agent is the development of acneiform eruptions. These eruptions seem to be reduced when dosed in combination with dabrafenib. Objectives To investigate the prevalence of acneiform eruptions in patients taking the MEK inhibitor trametinib, both alone and in combination with dabrafenib. Methods All patients enrolled in the trametinib alone (n = 13) or trametinib and dabrafenib combination (n = 30) clinical trials at a single site underwent a retrospective file review. The development and management of acne or acneiform eruptions was noted. Results In total, 77% of the trametinib group developed an acneiform eruption on the trial, while only 10% developed acneiform lesions in the combination trial. The patients were treated with oral doxycycline, topical antibiotics or topical antiseptic washes, with a good response. However the condition recurred if these treatments were ceased and the patient was still on trametinib therapy. Conclusions The MEK inhibitor trametinib is associated with the development of acneiform eruptions. When combined with dabrafenib the frequency of this side‐effect is reduced.